Neurorights: The Debate About New Legal Safeguards to Protect the Mind. - Istace, Timo (Issues in Law & Medicine)
Unprecedented efforts are made to research and develop technologies that are directly connected to the brain and allow us to access, monitor, investigate, assess, manipulate or stimulate neural processes. This exciting development holds many valuable prospects in the medical context and in other fields of daily life such as entertainment, security or criminal justice. However, it also raises major concerns among ethicists and human rights advocates, who argue that fundamental interests are put at risk as these neurotechnologies result in a growing accessibility and influenceability of the mind. In this article, I will describe how neurotechnologies may affect fundamental interests and how this concern led to the emergence of the concept of neurorights within human rights doctrine and policy. I will first outline the current state of the art and the prospects of neurotechnology, and discuss how this technology impacts the mind. Second, I will examine how this in turn may impact our mental privacy, autonomy, authenticity, personal identity, the self, and non-discrimination. Finally, I will show how these concerns prompted initiatives to establish neurorights as new human rights offering appropriate legal safeguards that protect the human mind against unwanted interference by neurotechnology.